THE IMPACT OF SURFACE BLUE SAPPHIRE MINING ON LAND USE LAND COVER TYPES IN THE MAMBILA PLATEAU - Karkarna, Mustapha Z.; Yusuf, Yusuf A.; Umar, Lawrence F. (FUDMA Journal of Sciences, 2020)
Information about patterns of Land use land cover (LULC) changes over time is not only important for a region’s management and planning, it is also required for a better understanding of the human dimensions of environmental changes on a regional scale. The study aimed to assess land use land cover change caused by artisanal mining of blue sapphire in some parts of Nguroje district on the Mambila Plateau, Taraba State, Nigeria. A change detection analysis was carried out using QGIS 3.8 and ENVI 5.0 software. Two different methods for change detection were applied; post-classification comparison (PCC) and land cover change detection. The major LULC classes present in the study area include bare land, forest vegetation, built-up areas, water body, agricultural land and grassland. The results of the change detection analysis showed that the natural forest cover 4.91% increased to 11.4% agricultural land decreased from 8.44 % to 6.50%, grassland decreased from 32.65% to 18.1%, built-up areas did not show a significant change, water body decreased from 0.14% to 0.12% while bare land increased from 53.74 % to 63.9 % all between 2007 to 2019 respectively. This study concludes that blue sapphire mining played a major role in natural resources degradation, which results in land-use change. The study suggests that for predicting future land-use change, methodologies are required that integrate and understand the processes affected by socio-economic and bio-physical drivers.